Photonic generation of microwave signal by beating a dual‐wavelength single longitudinal mode erbium‐doped fiber ring laser based on the polarization maintaining fiber bragg grating. Issue 2 (21st December 2012) - Feng, Suchun; Qi, Chunhui; Li, Qi; Peng, Wanjing; Gao, Song; Jian, Shuisheng
Abstract A single‐longitudinal‐mode (SLM) dual‐wavelength erbium‐doped fiber (EDF) ring laser based on one polarization maintaining fiber Bragg grating (PMFBG) is demonstrated.Due to the polarization hole burning enhanced by the PMFBG, the laser can be designed to operate in stable dual‐wavelength oscillation with a wavelength spacing of 0.182 nm at room temperature by adjusting a polarization controller. A section of unpumped EDF acting as a saturable absorber and a feedback fiber loop is used to ensure SLM operation in each of the two lasing lines. A microwave signal at 22.807 GHz is obtained by beating the dual‐wavelength fiber laser at a photodetector. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:347–351, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27280